2017
DOI: 10.1111/aec.12486
|View full text |Cite
|
Sign up to set email alerts
|

Extreme specialization to rocky habitats inTropiduruslizards from Brazil: Trade‐offs between a fitted ecomorph and autoecology in a harsh environment

Abstract: Ecomorphological theory indicates that different ecological requirements lead to different organismal designs. Given that species with equal requirements could not coexist, traits leading to more efficient use of resources may be selected to avoid competition among closely related syntopic species, generating specialized ecomorphs. We compared habitat use, diet, thermal biology and morphology among the syntopic Tropidurus semitaeniatus, T. helenae and T. hispidus in the Caatinga of Northeastern Brazil. Tropidu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Phylo-morphospace plots also suggested that the distantly related saxicoline G. borroloola / robusta and G. pamela complexes tend to have shorter toes and longer heads. Some of these phenotypic shifts, such as flattened body shape, typify rock-dwelling taxa in other lineages of Gehyra [ 14 ], other geckos [ 18 ], and other radiations of lizards [ 34 , 99 , 100 ]. However, while follow-up SURFACE and l1OU analyses identified divergent morphological regimes, they did not suggest convergence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phylo-morphospace plots also suggested that the distantly related saxicoline G. borroloola / robusta and G. pamela complexes tend to have shorter toes and longer heads. Some of these phenotypic shifts, such as flattened body shape, typify rock-dwelling taxa in other lineages of Gehyra [ 14 ], other geckos [ 18 ], and other radiations of lizards [ 34 , 99 , 100 ]. However, while follow-up SURFACE and l1OU analyses identified divergent morphological regimes, they did not suggest convergence.…”
Section: Discussionmentioning
confidence: 99%
“…Species’ habitats were categorised as saxicoline (shortened to “rock”) or generalist (“gen”) following previous convention [ 14 , 34 ]. This coding captures broad distributional patterns, rather than absolute microhabitat usage rules.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This argument is supported by studies that demonstrate the association of reptile species with the structure of the environment (Garden et al, 2007;Stumpel & Werf, 2012). Pelegrin et al (2017) described differences in microhabitat preferences in the Caatinga among Tropidurus hispidus, T. helenae and T. semitaeniatus, three sympatric species found in the Parque Nacional Serra da Capivara. Drymoluber brazili, Micrablepharus maximiliani and Tupinambis quadrilineatus, which were also found in other areas of Piauí, were recorded in areas with a predominance of Caatinga, Cerrado-Caatinga ecotone and Cerrado vegetation, respectively (Moura et al, 2010;Freitas et al, 2012;Silva et al, 2013).…”
Section: Comparison Between Species Composition In Middle Gurguéia Wimentioning
confidence: 99%
“…Several aspects of the ecology of species in the Tropidurus semitaeniatus Group have been studied (e.g., Kolodiuk et al 2010, Caldas et al 2015, Pelegrin et al 2017, Xavier and Dias 2017, Maia-Carneiro et al 2018. Several aspects of members of the group are phylogenetically conserved, such as specializations to live on rocks and in rock crevices, sexual dimorphism, sit-and-wait foraging, and clutch sizes of 1 or 2 eggs (with no correlation between clutch and body size).…”
Section: Introductionmentioning
confidence: 99%